International Pediatric Otolaryngology Group (IPOG) Consensus Recommendations: Congenital Cholesteatoma. Issue 3 (March 2020) - Denoyelle, Françoise; Simon, François; Chang, Kay W.; Chan, Kenny H.; Cheng, Alan G.; Cheng, Alan T.; Choo, Daniel I.; Daniel, Sam J.; Farinetti, Anne; Garabedian, Erea-Noël; Greinwald, John H.; Hoff, Stephen R.; et al.
Abstract : Objective: To provide recommendations to otolaryngologists and allied physicians for the comprehensive management of children who present with signs and symptoms of congenital cholesteatoma. Methods: A two-iterative Delphi method questionnaire was used to establish expert recommendations by the members of the International Pediatric Otolaryngology Group, on the preoperative work-up, the perioperative considerations, and follow-up. Results: Twenty-two members completed the survey, in 14 tertiary-care center departments representing 5 countries. The main consensual recommendations were: a precise otoscopic description of the quadrants involved, extensive audiological workup (bilateral tonal, vocal audiometry, and BERA), and a CT scan are required. Facial nerve monitoring and a combination of microscope and telescope are recommended for surgical removal. Clinical and audiological follow-up should be pursued yearly for at least 5 years. First MRI follow-up should be done at 18 months postoperatively if the removal violated the matrix. MRI follow-up duration depends on the initial extent of the cholesteatoma. Conclusion: The goal of preoperative and follow-up consensus from International Pediatric Otolaryngology Group participants is to help manage infants and children with congenital cholesteatoma. The operative techniques may vary, and experienced surgeons must perform these procedures.